2015
DOI: 10.1038/ejcn.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diet-related risk factors for chronic disease in male prisoners in a high secure prison

Abstract: Prevalence of diabetes and heart disease risk appear similar to the general population; however, obesity was lower and smoking higher. The data provide evidence that markers of chronic disease are present, with this the first study to describe the MS in prisoners. Food and nutrition policy in this setting is complex and should address the duty of care issues that exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 15 publications
0
25
0
3
Order By: Relevance
“…. Four of these studies included participants from both genders (largely male); one study included adult male participants only . Two of these studies were conducted among prison dischargees .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…. Four of these studies included participants from both genders (largely male); one study included adult male participants only . Two of these studies were conducted among prison dischargees .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were found through a search of grey literature. Therefore, a total of 16 studies were included in this review (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Figure 1 shows the steps followed in the literature search.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As desigualdades sociais, a diferença no acesso aos bens e aos serviços, a baixa escolaridade e a desigualdade no acesso à informação determinam, de modo geral, maior prevalência das doenças crônicas e dos agravos decorrentes da evolução dessas doenças (30) . Estudos mostram um aumento na obesidade e nos fatores de risco cardiovascular nas detentas, sugerindo que o encarceramento contribui para o desenvolvimento de doenças crônicas não transmissíveis (31)(32)(33)(34) . Além disso, as detentas têm maior probabilidade de desenvolver sobrepeso e obesidade do que mulheres da população geral e do que os detentos.…”
Section: Discussionunclassified